Impact of methyl Jasmonate on blueberry ripening fruits: assessment of cell wall thermal stability, nutritional parameters and antioxidant enzymatic activity - Vasquez-Rojas, Carlos; Muñoz-Vera, Marcelo; Flores, Sebastián; Betancourt, Mauricio; Castro, Ricardo I.; Ramos, Patricio; Laporte, Daniel; Parra-Palma, Carolina; Morales-Quintana, Luis (Frontiers in Plant Science, 2025)
IntroductionThe blueberry (Vaccinium spp.), recognized as one of the most significant horticultural crops globally, is valued for its rich bioactive compounds. In this study, we examine the effects of methyl jasmonate (MeJA) on blueberry, focusing on cell wall composition, nutritional properties, and antioxidant enzyme activity across two seasons (2022–2023). The objective is to evaluate the impact of MeJA treatments on fruit ripening dynamics and quality attributes.MethodologyBlueberry plants were treated with single (T1) and double (T2) MeJA applications. Thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC) were used to assess thermal degradation patterns of cell wall polymers. Biochemical evaluations included phenolic content, antioxidant capacity (DPPH and FRAP assays), and anthocyanin accumulation during ripening. Enzymatic antioxidant activities (APX, CAT, SOD, and POD) were also analyzed to determine oxidative stress responses.Results and discussionThermal degradation analysis revealed that green-stage fruits exhibited higher thermal stability than ripe fruits, with variations in pink-stage behavior between seasons. Biochemical assessments indicated a progressive decline in phenolic content and antioxidant capacity during ripening, whereas anthocyanin accumulation peaked in the blue stage, enhancing pigmentation. MeJA treatments significantly influenced antioxidant enzyme activity: T1 maximized APX, CAT, and SOD activities, while T2 amplified POD activity, contributing to oxidative stress tolerance and improved fruit quality. Furthermore, the modulation of hemicellulose fractions in TGA profiles suggests that MeJA helps maintain cell wall integrity, potentially reducing fruit softening during storage.ConclusionThese findings indicate that MeJA enhances fruit resilience during ripening while preserving key biochemical properties critical for postharvest management. The observed improvements in antioxidant capacity, enzymatic activity, and cell wall stability suggest that MeJA could be a valuable tool for optimizing postharvest handling, extending shelf life, and enhancing the marketability of blueberries. This work provides a preliminary framework for integrating MeJA into sustainable horticultural practices to meet consumer demand for high-quality functional fruits.